2006
DOI: 10.3143/geriatrics.43.693
|View full text |Cite
|
Sign up to set email alerts
|

Reperfusion therapy for acute myocardial infarction in elderly patients

Abstract: Although there has been great progress in reperfusion therapy, the role of coronary reperfusion for elderly patients with acute myocardial infarction has not been fully investigated. In general, mean age of the subjects in major trials was about 60 years old and approximately only 10 to 15% of patients were over age 75. On the other hand, large-scale registries such as the US national registry of myocardial infarction (NRMI) showed a higher prevalence of elderly (especially women) in the clinical setting. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In Japan, rates of CAD continue to increase in the elderly 14,15 and the impact on medical practice is huge. Important differences should be taken into account in elderly patients with CAD as compared with their younger counterparts: symptom presentation may be different, and complex coronary lesions, coexisting illness, and functional limitations are more prevalent, and the risk of revascularization procedures is generally increased.…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, rates of CAD continue to increase in the elderly 14,15 and the impact on medical practice is huge. Important differences should be taken into account in elderly patients with CAD as compared with their younger counterparts: symptom presentation may be different, and complex coronary lesions, coexisting illness, and functional limitations are more prevalent, and the risk of revascularization procedures is generally increased.…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial injuries that occur at reperfusion include arrhythmias, transient mechanical dysfunction of the heart, microvascular damage, and oxidative stress (OS) response (7). MI is mainly treated with drugs and surgery, but the prognosis remains unsatisfactory (8). A study showed that the levels of YKL-40 and sTNFR1 were associated with poor cardiac function and prognosis (9).…”
Section: Introductionmentioning
confidence: 99%